Problematika Pemungutan Pajak Reklame Di Kota Malang Berdasarkan Peraturan Daerah Kota Malang Nomor 4 Tahun 2023 (RechtJiva, 2024)
In this thesis, the author addresses the issues surrounding the collection of film/slide advertisement taxes in Malang City. Based on a preliminary survey conducted at the Regional Revenue Agency of Malang City, it was found that taxes for film/slide advertisements in Malang are not categorized under advertisement taxes but rather fall under entertainment taxes. However, in Malang City Regional Regulation Number 4 of 2023 regarding Regional Taxes and Levies, film/slide advertisements are included as one of the objects of advertisement tax. The research findings conclude that the collection of film/slide advertisement taxes in Malang City faces several problems. Firstly, the absence of regulations concerning the Rental Value of Advertisements (NSR) complicates the Regional Revenue Agency's ability to determine tax rates. Secondly, the Regional Revenue Agency of Malang City does not conduct specific collections for film/slide advertisement taxes; instead, they are combined with entertainment and arts service taxes, resulting in the absence of separate collections for film/slide advertisement taxes.